Identification of Thermophysical Parameters Using an Artificial Immune System - Dziatkiewicz, Jolanta; Poteralski, Arkadiusz (Computer Assisted Methods in Engineering and Science, 2023)
In this paper, the identification of thermophysical parameters using the hyperbolic twotemperature model is made. We investigate the influence of ultra-fast laser pulses on the heating of a thin metal film using this model. Two differential equations coupled with the electron-phonon coupling factor G are used. One of these equations concerns electron temperatures and the other addresses lattice temperatures. Appropriate initial and boundary conditions are imposed for this model. The finite difference method with a staggered grid is used to solve this direct problem. Temperatures for even nodes and heat fluxes for odd nodes are calculated. The results of the direct problem and results of the experiment are compared. In the optimization process, an artificial immune system is used.